CFD investigation of vapor transportation in a tubular solar still operating under vacuum. (August 2020) - Yan, Tiantong; Xie, Guo; Liu, Hongtao; Wu, Zhanglin; Sun, Licheng
Highlights: CFD simulation of tubular solar still under vacuum was performed. Vapor transportation with different geometric parameters was investigated. Different flow regimes were identified and compared with flow visualization photos. A correlation for predicting the value of Nusselt number was obtained. Abstract: Solar stills are one of the most promising and eco-friendly solutions for providing fresh water in arid regions. This study used computational fluid dynamics (CFD) modelling to investigate the effects of operating pressure p op and geometrical parameters on the performance of a Tubular Solar Still (TSS), with an emphasis on vapor flow in the enclosure. The simulation results indicated that water vapor has a higher circulation velocity when operated under vacuum compared with atmospheric conditions, resulting that the yield rate increased by more than 50% at p op < 60 kPa. Three distinct flow regimes were observed at different thermal Rayleigh numbers Ra T, which were identified as steady, periodic, and chaotic flow. Steady flow was observed at low Ra T, while periodic or chaotic flow was observed when Ra T exceeded 10 5 and water depth D w exceeded 0.4 r . The vapor flow in different regimes was validated by visualization experiments. Based on the simulation results, a correlation was obtained to predict the Nusselt number for a particular TSS design, which showed a deviation of -7.8−7.5% when compared with independent experimental datasets.